ELECTRONIC TEXTBOOKS AND VISUAL METHODOLOGICAL SUPPORT ARE THE GUARANTEE OF THE EFFECTIVENESS OF LEGAL EDUCATION - Kudaybergenova, T. (SCIENCE and SOCIETY, 2026)
The article discusses the fact that electronic textbooks and visual methodological support are a guarantee of the effectiveness of lessons, as well as law lessons.